Pengaruh Musik Terhadap Perkembangan Kognitif dan Melatih Fokus Pada Anak Usia Dini - Idarianty; Sri Hartati; Siti Safitri (Fakultas Pendidikan, Universitas Sultan Muhammad Syafiuddin Sambas, 2025)
This study investigates the significant influence of music on cognitive development and focus training in early childhood. The research highlights that music—particularly through engaging children's songs—plays a crucial role in enhancing cognitive skills. The literature review encompasses various studies demonstrating the positive effects of music on children's attention and working memory. These cognitive functions are essential for academic success, as children with better attention spans and memory capabilities tend to perform more effectively in tests and classroom activities. Moreover, the study indicates that participation in musical activities fosters social interaction and collaboration among children, further supporting their cognitive growth. Additionally, the findings reveal that music can help reduce anxiety and stress levels in young learners. A calm and pleasant musical background creates a soothing atmosphere, enabling children to concentrate more effectively on their learning tasks. This stress reduction is associated with improved cognitive performance, as children become less distracted by anxiety and more focused on their studies. The study also identifies gaps in the existing body of research and proposes that integrating music into early childhood education curricula may offer a comprehensive approach to supporting cognitive development. By incorporating music as an effective learning medium, educators, parents, and curriculum designers can enhance children's overall development, ensuring they are better prepared to face academic challenges. Ultimately, this study seeks to enrich the understanding of music's role in early childhood education and its potential benefits for both cognitive and emotional growth.